Civil/social approaches to the phenomenon of the alienation of the Gulf family - Alajmi, Amira Mohammed; Ibrahim, Abubaker Mohammed (Journal of Humanities & Social Sciences, 2024)
This study explores local and community approaches to addressing the phenomenon of family alienation in the Gulf countries. It examines the factors causing alienation and the resulting effects, while presenting effective strategies to mitigate this phenomenon. The focus is on how major social and economic transformations, such as rapid urbanization and changes in the labor market structure, affect the cohesion of Gulf families. The study also discusses the role of local and community initiatives in strengthening family bonds and supporting traditional cultural values as a basis for combating family alienation. The researcher followed the comparative descriptive method and text analysis.The results indicate that family alienation can stem from various factors, including changes in cultural and social values, weak communication among family members, and psychological pressures associated with economic and social expectations. The findings also suggest that alienation can lead to multiple psychological and social health problems, such as depression, social isolation, and poor academic and professional performance of family members. In the context of solutions.The study concludes that cooperation between the family and the community is necessary to address the challenges of family alienation in the Gulf countries. It emphasizes the importance of preserving cultural traditions and enhancing family relationships as essential factors to reduce this phenomenon.
Keywords: Local/Community Approaches; Family Alienation; Gulf Families